HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA DENGAN TINGKAT KECEMASAN DALAM MERAWAT ANGGOTA KELUARGA YANG MENGALAMI GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS SIJUNJUNG KABUPATEN SIJUNJUNG - Yuli Permata Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The number of patients with mental disorders as many as 75 people in 2017 in the working area of Health Center Sijunjung Regency Sijunjung with the number of patients teraty mental disorder in 2017 patients mental disorder is in the third position with the number of patients 75 people in the Working Area Health Center Sijunjung. Family is very influential on the healing process of family members who have mental disorders, because the family often feel anxiety in caring for family members who suffer from mental disorders. This study aims to determine the relationship of knowledge and attitudes of families with anxiety levels in caring for family members who have mental disorders. This research uses corelatif study method. The sampling technique used is multistage sampling involving 48 respondents, then processed using chi-square test. Statistical test results obtained value ρ value = 0,000 (ρ